Isolation of Integrin‐Based Adhesion Complexes. Issue 1 (2nd March 2015) - Jones, Matthew C.; Humphries, Jonathan D.; Byron, Adam; Millon‐Frémillon, Angélique; Robertson, Joseph; Paul, Nikki R.; Ng, Daniel H. J.; Askari, Janet A.; Humphries, Martin J.
Abstract: The integration of cells with their extracellular environment is facilitated by cell surface adhesion receptors, such as integrins, which play important roles in both normal development and the onset of pathologies. Engagement of integrins with their ligands in the extracellular matrix, or counter‐receptors on other cells, initiates the intracellular assembly of a wide variety of proteins into adhesion complexes such as focal contacts, focal adhesions, and fibrillar adhesions. The proteins recruited to these complexes mediate bidirectional signaling across the plasma membrane, and, as such, help to coordinate and/or modulate the multitude of physical and chemical signals to which the cell is subjected. The protocols in this unit describe two approaches for the isolation or enrichment of proteins contained within integrin‐associated adhesion complexes, together with their local plasma membrane/cytosolic environments, from cells in culture. In the first protocol, integrin‐associated adhesion structures are affinity isolated using microbeads coated with extracellular ligands or antibodies. The second protocol describes the isolation of ventral membrane preparations that are enriched for adhesion complex structures. The protocols permit the determination of adhesion complex components via subsequent downstream analysis by western blotting or mass spectrometry. © 2015 by John Wiley & Sons, Inc.